Financiamento público da saúde: Uma história à procura de rumo - Sérgio F. Piola; Andrea Barreto de Paiva; Edvaldo Batista de Sá; Luciana Mendes Santos Servo (Instituto de Pesquisa Econômica Aplicada (IPEA), 2013)
– This article provides an analysis of policies adopted to ensure adequate funding to public health care in Brazil as determined by the 1988 Federal Constitution. Issues related to the tripartite funding of the SUS, the decentralization of federal financial resources to subnational levels of government and the recent regulation of the Constitutional Amendment (CA) 29/2000 are discussed. The CA 29/2000 led to an increase in financial resources to fund health care provided by the SUS from 2.89% of the GDP in 2000 to 3.91% in 2011. The recent regulation, Law 141/2012, helped define more precisely what should and what should not be considered health care provided by the SUS. Unfortunately, no change has been proposed regarding the proportion of federal revenues that should be committed to public health care. The definition of equitable criteria for the distribution of federal financial resources to subnational levels of government is also a pending issue.
Keywords: H51; I10; 330; health care funding; regulation of the Constitutional Amendment 29; criteria for the distribution of financial resources